Tax dynamics of the unified property tax in Colombia: case studies in Cali, Bogota, Medellin and Ibagué - Gallego Cossio, Laura
The unified property tax is a municipal tax with which it is expected to collect money through the liquidation that every owner and possessor of a property must make for the goods located in the jurisdiction of the municipality. It is levied on the real estate and is generated by the existence of all property, its taxable base is centered on the cadastral appraisal and it is an endogenous income of the property of the municipalities; the entities in charge of its administration are all the municipalities that generate the collection and control, likewise they are in charge of providing tax benefits to the taxpayer at the time of generating the payment. The purpose of this research is to analyze the historical and legal framework of this tax burden with the objective of evidencing the evolution it has had over the years and its impact in the different cities, through the identification of the historical traceability of the unified property tax in Colombia. The methodology of the study is of an explanatory type, generating answers to the different questions why and how of the event studied, as well as revealing laws and principles that generate explanatory models and theories. The results of the research present the legal reforms that have impacted the collection of the tax and its effect in the main municipalities of the country such as Cali, Bogotá, Medellín, Ibagué and Bucaramanga; likewise, characterizing the procedural dynamics in the liquidation, presentation and payment of the property tax with a case study in the city of Ibagué, where a fiscal deficit in the collection was identified due to the existence of 217. 176 properties that are obliged to contribute to the municipality, of which 76,018 properties have not generated the payment of the tax, affecting the municipal budget of Ibagué to generate investments in the city and thus cover the different expenses, since it is a significant figure of portfolio to be collected.